PELATIHAN KETERAMPILAN SOSIAL UNTUK MENGATASI KECEMASAN SOSIAL PADA ANAK MENJELANG BEBAS DI LPKA - Heni Mulyati; Susi Fitri; Zarina Akbar (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
This research is a literature study on social anxiety experienced by Class II Jakarta-assisted Child Development Institutions (Child Development Institutions) when they are free. Previously, LPKA was widely known by the public as Child Prison. Study of the theory of experts and related studies are used as the basis for reinforcing assumptions in the field. Social anxiety in this study focused on children approaching free in Class II LPKA Jakarta. The results of the study indicate the existence of social anxiety experienced by children approaching free. One technique that can be used to overcome social anxiety is social skills training. There are three aspects of social anxiety, namely: fear of negative evaluation, social avoidance and new distres, and social avoidance and general distres. Social skills training uses the following techniques: (1) Instructions, (2) Modeling, (3) Exercises, (4) Training, feedback, reinforcement, and (5) Homework. The next interesting study to be developed is the effectiveness of social skills training in overcoming social anxiety of LPKA children before being free.